PEMBERDAYAAN EKONONMI LOKAL MELALUI PELESTARIAN HUTAN RAKYAT (Studi Kasus Hutan Rakyat Desa Regunung Kabupaten Semarang) - Darwanto, Darwanto (MEDIA EKONOMI & TEKNOLOGI INFORMASI, 2011)
Regunung village is one of village in Semarang regency that poses hutan rakyat (a forest that belong to society or people around the forest environment). Hutan rakyat is a result of sengonisasi program on society land. Society will replace the land function and change the plant because sengon plant has high economic value. Result of this study shows that Sengonisasi program of hutan rakyat in Regunung can increase welfare and decrease erosion degrees. Although in another village this program has not succeed already caused of nature condition that is not appropriate for sengon plant.Keyword: hutan rakyat economy empowerment, sengon.